An accurate fully automated panel of plasma biomarkers for Alzheimer's disease. Issue 4 (11th August 2022) - Palmqvist, Sebastian; Stomrud, Erik; Cullen, Nicholas; Janelidze, Shorena; Manuilova, Ekaterina; Jethwa, Alexander; Bittner, Tobias; Eichenlaub, Udo; Suridjan, Ivonne; Kollmorgen, Gwendlyn; Riepe, Matthias; von Arnim, Christine A.F.; et al.
Abstract: Introduction: There is a great need for fully automated plasma assays that can measure amyloid beta (Aβ) pathology and predict future Alzheimer's disease (AD) dementia. Methods: Two cohorts ( n  = 920) were examined: Panel A+ ( n  = 32 cognitively unimpaired [CU], n  = 106 mild cognitive impairment [MCI], and n  = 89 AD) and BioFINDER‐1 ( n  = 461 CU, n = 232 MCI). Plasma Aβ42/Aβ40, phosphorylated tau (p‐tau)181, two p‐tau217 variants, ApoE4 protein, neurofilament light, and GFAP were measured using Elecsys prototype immunoassays. Results: The best biomarker for discriminating Aβ‐positive versus Aβ‐negative participants was Aβ42/Aβ40 (are under the curve [AUC] 0.83–0.87). Combining Aβ42/Aβ40, p‐tau181, and ApoE4 improved the AUCs significantly (0.90 to 0.93; P < 0.01). Adding additional biomarkers had marginal effects (ΔAUC ≤0.01). In BioFINDER, p‐tau181, p‐tau217, and ApoE4 predicted AD dementia within 6 years in CU (AUC 0.88) and p‐tau181, p‐tau217, and Aβ42/Aβ40 in MCI (AUC 0.87). Discussion: The high accuracies for Aβ pathology and future AD dementia using fully automated instruments are promising for implementing plasma biomarkers in clinical trials and clinical routine.